PERILAKU GREEN BEHAVIOUR DENGAN PEMBELAJARAN EKOLITERASI PENDIDIKAN KARAKTER ANAK USIA DINI - Rida Nurfarida; Pandue; Aan Hasanah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The purpose of this study is that early childhood already has Green Behavior characters by learning ecoliteracy through assignment methods, audiovisuals, habituation, and direct practice. Giving daily examples at school and home in the community. The research method used is a qualitative survey analysis method. Researchers distributed survey questionnaires to respondents to obtain data relevant to the research. Survey analysis collects data based on several research instruments distributed to certain parties who are the sources of research. The source of this research is the main source consisting of teachers, while the second source is the reference or relevant literature studies. Data obtained from the distribution of questionnaires are collected and then displayed in data displays to be then processed based on the right theory to obtain the right conclusions., a research procedure that produces descriptive data in the form of written or oral data from people and behaviors that can be observed as the object of research, deepening by observing, reviewing documents and interviews. The research results are 1) Children are taught to love animals that are beneficial and not harmful to humans. 2) Children are taught to throw garbage in its place 3) Children are taught to sort waste according to organic and non-organic types 4) Children are taught about water, consisting of ways to save and the benefits of saving water; Keeping the environment clean, the benefits of protecting the environment and natural resources. 5) Teaching about electricity, consisting of how to save and the benefits of saving electricity; Results Develop As Expected. 6) About plants, which consists of planting and watering, not picking plants carelessly, and the benefits of plants for life. 7) Keeping the environment clean, the benefits of protecting the environment and natural resources. The value of the results of character education is that children develop according to expectations.